Acute biliary pancreatitis: preliminary contributions from a prospective study - Flores, Jorge; Samaniego, Castor; Giménez, Alejandro; Burguez de Iturbe, Clara; Girala, Mario; Frutos, Benito; Filizzola, Roberto (Cirugía del Uruguay, 1998)
The preliminary results of a prospective study performed in the Surgica! Department of the "Facultad de Ciencias Médicas de la Universidad Nacional de Asunción. Paraguay': is presented here. The series inc!udes 54 patients with acute biliary pancreatitis confirmed by !aboratory and image studies, who underwent examination by the G!asgow sea/e from the beginning. Two different groups were identified in this way: one wite less than three positive factors (light forms, 33 cases), an another with three or more positive forms (severe forms, 21 cases).